16S rRNA-Based Identification of a Glucan-Hyperproducing Weissella confusa. (16th March 2011) - Shukla, Shraddha; Goyal, Arun
Abstract : A gram-positive, nonmotile, irregular, short, rod-shaped new strain of Weissella confusa bacterium was isolated from fermented cabbage. The isolate was physiologically and biochemically characterised. The 16S rDNA was amplified by polymerase chain reaction (PCR). The isolate was identified as Weissella confusa (GenBank accession number: GU138518.1) based on nucleotide homology and phylogenetic analysis. The isolate produces glucansucrase when grown in sucrose-supplemented culture medium which catalyses glucan formation. This novel isolate possesses high capacity of industrial use due to its high productivity of glucan (34 mg/mL) as compared to other strains reported. The optimum temperature for glucansucrase production was 25°C. The shaking condition gave an enzyme activity of 6.1 U/mL which was 1.5 times higher than that given by static condition (4.1 U/mL). The temperature 35°C, pH 5.4, and ionic strength 10–20 mM were optimum for enzyme assay. This investigation unraveled the abundance of industrially valuable microflora of the north east India.